Comparison of Flutamide and Metformin in Overweight-Obese Women with Polycystic Ovary Syndrome Following a Hypocaloric Dieting - S Esmaeilzadeh (Babol University of Medical Sciences, 2010)
BACKGROUND AND OBJECTIVE: Polycystic ovary syndrome is one of the most common items in endocrine diseases and involved patients are at the risk of diabetes and atherosclerosis and cardiovascular disease. The most common clinical features of PCOS are insulin resistance, hyperandrogenemia, non ovulation and infertility. Since obesity is the most common cause of insulin resistance and hyperandrogenemia, so this study was designed to evaluate the effects of weight reduction and treatment with metformin and flutamide on insulin resistance indices and hyperandrogenism and lipid serum in overweight-obese PCOS patients. METHODS: This double blind clinical trial study was performed on 40 overweight-obese women with PCOS. After a one month diet, according to a control trial double blind design, the patients were randomly allocated to treatment with placebo, metformin (500mg/TDS) and flutamide (250 mg/BID) for the following 6 months while continuing hypocaloric dieting. At baseline and at the end of the study anthropometric parameters, hirsutism and menses, sex hormones, SHBG, lipid and insulin sensitivity determinations were measured and compared in two groups.FINDINGS: Metformin (12.2±6.07 kg) has a significant effect in decreasing body weight (p=0.000), BMI (p=0.000), waist circumference (p=0.000) and hip circumference (p=0.000) and hirsutism (p=0.000), total testosterone (p=0.032). Flutamide (6.5±5.1 kg) has effectively decreased body weight (p=0.000), BMI (p=0.000), waist circumference (p=0.000) and waist/hip circumference (p=0.005) and hirsutism (p=0.000), total testosterone (p =0.024), cholesterol (p=0.011) and LDL levels (p=0.013). CONCLUSION: The results of this study showed that safe drugs such as metformin and flutamide reduced in anthropometric indices and hirsutism. Metformin has been more effective in reducing weight, BMI, waist and hip circumference rather than flutamide.